Coping with the Diversity of Student Aptitudes and Interests - Duggal, Vijaya G. (American Economic Review, 1987)
There is no dispute in the economic profession that a background in quantitative methods is essential for undergraduates majoring in economics. What may not be so clear is what is expected of the student who has completed the requirements in quantitative methods. Is the student expected to be able to advance the discipline of statistics and econometrics, or is he or she merely expected to be able to use the tools to find quantitative solutions to issues he might face in the profession? When the question is posed in this manner, the majority will consent to the second expectation. Do we, in the quantitative courses we teach, prepare them adequately to fulfill this expectation, or are we as instructors secretly driven to expose our students to all mathematical derivations that we studied in graduate school? If we dealt with only the brightest of students in an average university, it would not matter how we approached the subject, for these students have the ability to comprehend and absorb whatever they are taught. For the average student, however, it is important to limit ourselves to what we think should be their essential repertoire. This paper is not intended to cover the teaching of quantitative methods in a comprehensive manner, or to provide any systematic revaluation. Instead, it focuses on some changes in our teaching methods that may enhance certain segments of a quantitative course. Essentially, I find that we spend too much time on statistical theory on the one hand, and hand calculations on the other, at the expense of conceptual understanding of the material. Our method of teaching needs to be modified more than it has been in order to exploit advances in computer technology. There is a need for greater emphasis on the relevance of the material and practical applications of the tools we present.